2018
DOI: 10.1109/tcomm.2018.2837909
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Trading for Satellite Communication Systems with Dynamic Bargaining

Abstract: With the rapid development of modern satellite communications, broadband satellite services are experiencing a period of remarkable growth in both the number of users and the available bandwidth. More efficient spectrum management schemes require deeper investigation in order to meet the everincreasing demand for broadband spectrum. In this paper, we propose a band allocation method for multibeam satellite systems by introducing a market-driven pricing mechanism. Instead of adopting static and fixed band selli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…The human-oriented mobile perception services can enhance the range of perception and reduce perception hole by introducing social computing or mobile computing theory and analyzing perception data. Rea et al devised an embedded action-identified system on the basis of mobile perception mechanism, so as to further promote the applications of mobile perception in smart circumstance, monitoring, crisis response and military field [34].…”
Section: Information Fusion and Mobile Cognitionmentioning
confidence: 99%
“…The human-oriented mobile perception services can enhance the range of perception and reduce perception hole by introducing social computing or mobile computing theory and analyzing perception data. Rea et al devised an embedded action-identified system on the basis of mobile perception mechanism, so as to further promote the applications of mobile perception in smart circumstance, monitoring, crisis response and military field [34].…”
Section: Information Fusion and Mobile Cognitionmentioning
confidence: 99%
“…Market-driven mechanism consisted of auction-based or pricing-based approach can efficiently redeploy the scarce resource, balance the demands and even attract potential participants [34,35]. Auction theory received considerable attention for solving the problem of maximizing utilization in the case of resource scarcity, which is with uncertainty about the peculiar information and achieving competitive fairness [36].…”
Section: Related Workmentioning
confidence: 99%
“…The authors in [10] provided the closed-form formula of the outage probability (OP) for the considered system in the presence of interference power constraints imposed by multiple adjacent terrestrial primary users (PUs). The authors in [11] studied the interweave architecture for HSTCN to allow the satellite share idle spectrum with terrestrial networks. They indicated that cognitive satellite systems can not only improve the spectrum utilization but also benefit their operational revenues.…”
Section: Introductionmentioning
confidence: 99%